Biotectonics of Sulawesi: Principles, methodology, and area relationships - Michaux, Bernard; Ung, Visotheary (Zootaxa, 2021)
Biotectonics is an approach to historical biogeography based on the analysis of independently derived biological and tectonic data, which we demonstrate using the island of Sulawesi as an example. We describe the tectonic development of Sulawesi and discuss the relationship between tectonic models and phylogenetic hypotheses. We outline the problem of interpreting areagrams based on single phylogenies and stress the importance of combining all available data into a general areagram. We analysed the distributions of Sulawesi area of endemism endemics (AEEs) using 30 published phylogenies, which were converted into paralogy-free taxon-area cladograms using the programme LisBeth (Zaragüeta-Bagalis et al. 2012) from which Adam’s consensus trees were constructed using PAUP (Swofford 2002). The results of our analyses show that the relationship between the areas of endemism is congruent with the terrane history of the island. A further 79 phylogenies of Sulawesi species with extralimital distributions were analysed to determine area relationships of Sulawesi within the broader Indo-Pacific region. We demonstrate the utility of data partitioning when dealing with areas that are geologically and biologically composite by showing that analysing Asian and Australasian elements of the Sulawesi biota separately produced general areagrams that avoid artifice and are interpretable in the light of current tectonic models.